A combination of histological analyses and uniaxial tensile tests to determine the material coefficients of the healthy and atherosclerotic human coronary arteries. Issue 2 (April 2015) - Karimi, Alireza; Navidbakhsh, Mahdi; Shojaei, Ahmad
Highlights The key role of fiber orientation was explicitly added into a proposed material model. The CNOM was used to determine the material coefficients of human coronary samples. Regardless of loading direction, atherosclerotic arteries were stiffer than healthy ones. The optimized fiber angles were well compared to the experimental histological data. The stored energy function of the healthy arteries was higher than that of atherosclerosis.